Drying kinetics for vegetable seeds with Zeolite beads - BASHIR, AKHOON ASRAR; SINHA, J P; JHA, G K; CHOPRA, SANGEETA (The Indian Journal of Agricultural Sciences, 2016)
Drying seeds and maintaining low seed moisture content is critical in hot and humid climatic conditions with conventional drying method. In this study Zeolite beads which are inert adsorbent materials have been used for drying tomato and onion seeds. Response Surface Methodology was employed to optimize the parameters of drying for seeds of tomato cv. Pusa Ruby and onion cv. Nasik Dark Red in Central Composite Rotatable Design (CCRD). The effect of initial moisture content, residence time and seed-bead ratio on final moisture content, germination percentage and vigour was determined. Five levels of initial moisture content (8.6 to 15.4 %db), residence time (1.3, 4, 8, 12, 14.7 h) and seed-bead ratio (1:0.33, 1:0.5, 1:0.75, 1:1, 1:1.17) were used for the experiment. Second degree polynomial models were found suitable for each response, viz. final moisture content germination percentage and vigour. The desirability index technique was used to predict the ideal drying condition. At the optimum values of 11.84% initial moisture condition, 10.8 h residence time and 1:0.5 seed-bead ratio, final moisture was 3.94%, germination percentage was 76.99% and high vigour for tomato seeds. Similarly, at optimum values of 13.62% initial moisture condition, 6.52 h residence time and 1:0.62 seed-bead ratio, final moisture was 5.55%, germination percentage was 71.08% and high vigour for onion seeds.